Identification of field and gardenpea (Pisum sativum) varieties using RAPD and ISSR markers - R.K. KAPILA; S. NARYAL; K.C. DHIMAN; S.K. SINGH; J.K. SHARMA (Seed Research, 2026)
Identification of seven varieties of garden and field pea (Pisum sativum L.) currently under seed multiplication chain in Himachal Pradesh was undertaken using 40 random decamer and 9 ISSR primers. A total of 251 amplicons including 111 RAPDs and 70 ISSRs bands were amplified. The ISSR markers exhibited better polymorphism and resolving power as compared to RAPDs. High pair-wise genetic similarity estimates ranging from 0.50 to 0.86 indicated narrow genetic base of the set of varieties. Clustering analysis based on pooled data grouped 7 varieties in 3 main groups. Four gardenpea varieties comprised one main group, whereas a field pea along with one gardenpea variety constituted other group. Field pea variety, Rachna, was most divergent from other varieties and did not group with any other varieties. All the 7 varieties were resolved completely using variety specific and/or other polymorphic markers amplified using single ISSR and RAPD primers, namely UBC 843 and OPJ 14, respectively. Four random decamer and 6 ISSR primers were identified as potential ones that could alone distinguish 5 or more varieties, out of a set of total 7 varieties. Study indicated possible use of variety-specific amplicons in developing diagnostic kits for identification of current set of pea varieties under cultivation in Himachal Pradesh.